Pengaruh Bermain Bola Plastik Kecil terhadap Kemampuan Gerak Manipulatif Anak - Syarifah Mutmainah Van Gobel; Icam Sutisna (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2019)
This research was conducted because of the low ability of children in manipulative motion. The purpose of this study was to obtain empirical data about the Effects of Playing Small Plastic Balls on Children's Manipulative Motion Capabilities. The research method used is quantitative research with one group pretest posttest design. Data collection techniques used are performance tests. The results showed the average value of the pretest or before treatment was 11.05 and the average value of the posttest after treatment was 36.80. Hypothesis testing using non-parametric statistics in this case is the Wilcoxon test. The basis for decision making in the Wilcoxon test is, if the Asymp.sig value <0.05, then H1 is accepted and if the Asymp.sig value> 0.05, then H1 is rejected and based on test output statistics, it is known asymp.sig.n ( 2-tailed) worth 0,000. Because the value is 0,000 <0.05, the hypothesis is accepted.